2010
DOI: 10.1677/erc-09-0153
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-R and its association with PI3K/AKT signaling pathway in papillary thyroid carcinoma

Abstract: The putative role of leptin and its receptor (Ob-R) in the pathogenesis of various primary human malignancies has been reported; however, their role in papillary thyroid cancer (PTC) has not yet been evaluated. We investigated the role of Ob-R in a large tissue microarray cohort of PTC followed by in vitro studies using a panel of PTC cell lines. Ob-R overexpression was seen in 80% PTCs and was significantly associated with poor disease-free survival (PZ0.0235). PTCs that overexpressed Ob-R showed a aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 47 publications
8
60
3
1
Order By: Relevance
“…This is in keeping with the observation of others (13)(14)(15)(16)(17). We and others have shown that papillary thyroid cancer with expression of leptin receptor and/or leptin is associated with the risk of nodal metastasis (21,22). The same oncogenic signaling cascade initiating transforming events in thyroid cancer cells also sustains their motile and invasive properties (33).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in keeping with the observation of others (13)(14)(15)(16)(17). We and others have shown that papillary thyroid cancer with expression of leptin receptor and/or leptin is associated with the risk of nodal metastasis (21,22). The same oncogenic signaling cascade initiating transforming events in thyroid cancer cells also sustains their motile and invasive properties (33).…”
Section: Discussionsupporting
confidence: 89%
“…Although papillary thyroid cancer expressing leptin receptor and/or leptin is associated with larger tumor size (21,22), this study does not support the hypothesis that leptin promotes cell proliferation in thyroid cancer. Uddin et al (22) demonstrated that leptin could stimulate cell proliferation and inhibit apoptosis in B-CPAP and 8505C cell lines via the activation of PI3K/AKT signaling pathway.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Leptin was shown to promote cell migration in PTC cells, while inhibiting the migration of follicular and anaplastic thyroid cancer cells (157). Other in vitro studies demonstrated that leptin stimulates a more aggressive PTC phenotype by putative activation of the PI3K/AKT pathway (158), and also promotes the de-differentiation of thyroid tumor cells via the JAK2/ STAT3 signaling pathway (159). The possibility that these effects might result in distinct tumor presentations and disease courses remains purely theoretical.…”
Section: Thyroid Cancer In Obese Patientsmentioning
confidence: 99%
“…There are many evidences that obesity can cause poor prognosis of many cancers such as ovarian cancer, leukemia, papillary thyroid cancer, and colon cancer [Dignam et al, 2006;Uddin et al, 2010]. Epidemic studies showed that severe obesity (BMI >35 kg/m 2 ) caused increased mortality and recurrence of colon cancer [Dignam et al, 2006;Jacobs et al, 2007].…”
Section: Evidence For the Poor Prognosis Of Obe-sity-associated Cancermentioning
confidence: 99%